2014
DOI: 10.1097/mbc.0000000000000089
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α –308G/A gene polymorphism in Egyptian children with immune thrombocytopenic purpura

Abstract: Immune thrombocytopenic purpura (ITP) is an autoimmune disease characterized by increased platelet destruction. Although the cause of ITP remains unclear, it is accepted that both environmental and genetic factors play an important role in the development of the disease. Children with ITP have a T-helper 1-type cytokine pattern with elevated levels of tumor necrosis factor-alpha (TNF-α) as in most autoimmune diseases. Researchers have shown that polymorphism in the TNF-α gene at position -308 affects gene tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The polymorphic A allele frequency was significantly higher in ITP patients than in the controls, conferring almost two-fold increased ITP risk [27]. However, similar to our results, both the frequency of TNF-a (-308) G/A and A/ A as well as A allele frequency were not significantly different in newly diagnosed than chronic patients with ITP.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The polymorphic A allele frequency was significantly higher in ITP patients than in the controls, conferring almost two-fold increased ITP risk [27]. However, similar to our results, both the frequency of TNF-a (-308) G/A and A/ A as well as A allele frequency were not significantly different in newly diagnosed than chronic patients with ITP.…”
Section: Discussionsupporting
confidence: 67%
“…Saitoh et al [14] found no significant relationship between IL-17F 7488TT/TC and treatment response, including CR, R, and corticosteroid dependence as well as the study of El Sissy et al [27] who found no difference in treatment response for those harboring TNF-a (-308) polymorphic genotype between the newly diagnosed and chronic patients with ITP.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Higher levels of TNF have been reported in the plasma/serum from ITP patients,(Culic et al , 2013; Jernas et al , 2013; Talaat et al , 2014) although TNF expression levels in specific ITP cell types, such as CD4+ T lymphocytes, has not been examined. Interestingly, ITP patients have an increased frequency of TNF −308 A polymorphic allele associated with higher TNF-α production (Pehlivan et al , 2011; Sarpatwari et al , 2011; El Sissy et al , 2014). TNF binds to two distinct receptors: TNFRSF1A (TNFRI, p55) and TNFRSF1B (TNFRII; p75) (Locksley et al , 2001).…”
mentioning
confidence: 99%
“…It is also important to note that the presence of H. pylori increases TNF-α expression, a process which reflects the interaction between this inflammatory mediator and gastric carcinogenesis [8]. Polymorphisms that increase TNF-α expression have now been associated with autoimmune diseases and cancer [9][10][11].…”
Section: Introductionmentioning
confidence: 99%